Implementasi Metode Received Signal Strength Indication dan Quality of Service Terhadap Analisis Kualitas Jaringan Wireless di CV Java Media Perdana Pati - Prahara, Imanuel Noval Amanda; Widiasari, Indrastanti R. (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The purpose of this study was to find out and determine the value of Quality of Service and the Receive Signal Strength Indicator of the CV Java Media Perdana internet network, Dukuhseti District, Pati Regency. This research is a case study type research on the strength of the internet network at CV Java Media Pratama. This research begins with the stages of data collection on Quality of Service (QOS) and Receive Signal Strength Indicator (RSSI). Mesurement are based on troughput, Packet loss, Delay (latency) and jitter. The four measurement methods show different result in each place and the distance between measuring instrument and the router in that place. The performance of a network has several parameters. The Throughput parameter shows that the average measurement results are bad to good enough to excellent (very good). On the Packet loss parameter in all places shows very good data. The average Delay (latency) parameter or almost all test locations have very good results. In the jitter parameter, there are several places that have poor results, only a few places have good results. Network quality is not affected at a distance from the host server. There is a place that is far from the server or CV Java Media Perdana office but has good signal quality.